THU0523 Tocilizumab in Refractory Uveitis Associated to Juvenile Idiopathic Arthritis. Multicenter Study of 13 Cases. (9th June 2015) - Santos Gόmez, M.; Calvo-Río, V.; Blanco, R.; Calvo, I.; Maíz, O.; Atanes, A.; Bravo, B.; Modesto, C.; Díaz Soriano, G.; Riancho-Zarrabeitia, L.; Palmaou-Fontana, N.; González-Gay, M. Ά.
Abstract : Objectives: To assess the efficacy of Tocilizumab (TCZ) in refractory uveitis associated to juvenile idiopathic arthritis (JiA). Methods: Multicenter study of uveitis related to JiA and refractory to at least a) one standard synthetic immunosuppressive drug and, b) 1 anti-TNFα drug. Results: We studied 13 patients/24 eyes (2 men/11 women) with a mean age of 20.38±9 years (range 8-38). The most frequent ocular pattern was anterior uveitis (n=11), bilateral (n=11), and chronic (n=13). Besides corticosteroids and before TCZ onset, they had received methotrexate (n=11), cyclosporine A (n=5), mycophenolate (n=1) and leflunomide (n=1). The first biologic treatment was: adalimumab (ADA) (n=6) (40 mg/sc/2 weeks), infliximab (IFX) (n=3) (5 mg/kg/i.v./every 6-8 weeks) and etanercept (ETN) (n=4). Before TCZ onset they had been switched to a second biologic drug (n=11) (most of them due to inefficacy), a third (n=5), a fourth (n=3) and even a fifth biologic therapy (n=1). The median of the duration of uveitis before the onset of TCZ was 122 months [IQR 42-178]. TCZ was used at a conventional dose (8 mg/kg/4 weeks) in most cases and combined in all cases (MTX=7, LFN=4, CsA=1, MMF=1). Improvement from baseline to 1 year was observed in: a) Visual acuity: from 0.46±0.35 to 0.52±0.37 (p=0.007); b) Anterior chamber cells from a median [IQR] of 1 [0.5-2] to 0 [0-0] (p=0.001), c) vitritis from 0 [0-1] to 0 [0-0] (p=0.06) and d) Macular thickness from a mean of 277±127 to 234±32 microns (p=0.04), and this allowed to taper corticosteroids from a mean of prednisone of 15±14 mg/day to 6±5 mg/day. After a mean follow-up of 15.2±8.3 months, ocular remission was achieved in 9 of 13 patients. The most severe adverse events of TCZ were severe thrombocytopenia (1), pneumonia (1), viral conjunctivitis and bullous impetigo (1). Conclusions: Tocilizumab seems to be effective in refractory uveitis related to JiA. Disclosure of Interest: None declared